Hugh, Son of Robert the Pious (1007–1025) as Rex associatus in the Light of Rodulfus’ Glaber Chronicle - Pietranik, Monika (Vade Nobiscum, tom XX/2019: Studia z historii politycznej i wojskowej, 2019)
The practice of the designation of the ruler’s son during his father’s lifetime was present and extremely important from antiquity on as a part of the Diocletian’s tetrarchy. In t he M iddle A ges t he C arolingians, C apetians, O ttonians, S alians a nd o ther d ynasties continuated to pursue this model, changing it and adapting for their present purposes. However, the problem of associatio in regem is present and explored. in modern medieval studies, the majority of historians focuses on the system as a whole, considering the purposes of this practice’s use and it’s dependance on the ruler’s weakness. The aim of this article is to examine toroughly the case of Hugh, son of Robert the Pious, described by Raoul Glaber as a rex associatus and define his social and ideological functions in the rule system comparing it with other, similiar examples. Such a study will enable us to draw more general conclusions concerning the particular situation of a rex associatus at his father’s court and in the whole kingdom, distinguishing the universal aspects of the problem from the exceptional ones, which resulted from specific conditions, different for each rex associatus.